2002
DOI: 10.1111/j.1469-8749.2002.tb00327.x
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor dysfunction in cerebral visual impairment following perinatal hypoxia

Abstract: The aim of the study was to describe ocular motility in a sample of 56 patients affected by cerebral visual impairment (CVI) of hypoxic‐ischemic origin. The sample consisted of 56 participants (37 males and 19 females), ranging in age from 2 to 16 years. In all cases CVI was associated with MRI‐verified damage of the cerebral visual system. A complete ophthalmologic and neurological assessment was performed. Behaviour of gaze was studied in four conditions: during scanning of the surrounding environment, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 34 publications
2
37
0
2
Order By: Relevance
“…These results concur with the findings of other studies performed in children with neurological impairments, although some report an even higher prevalence of CVI. 12,[20][21][22] Of the participants diagnosed with CVI, 88.46% were classified at VCS levels 1 to 3, as were 84% of those participants diagnosed with optic atrophy. The group without visual impairment were all classified at level 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…These results concur with the findings of other studies performed in children with neurological impairments, although some report an even higher prevalence of CVI. 12,[20][21][22] Of the participants diagnosed with CVI, 88.46% were classified at VCS levels 1 to 3, as were 84% of those participants diagnosed with optic atrophy. The group without visual impairment were all classified at level 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…However, nystagmus is an eye movement disorder that also commonly occurs in individuals with CVI. 21,22 Thus, RTF delays in the group with CVI could originate from either visual processing impairments or ocular motor instabilities. These instabilities were quantified and it was found that GFA values were only moderately increased in the group with CVI compared with the group with congenital nystagmus and the comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with WMDI can exhibit a wide spectrum of visual symptoms, ranging from early onset esotropia to severe cerebral visual impairment (Cioni et al 1997). Findings of subnormal but slowly improving VA, crowding (Pike et al 1994) and eye motility disorders (Salati et al 2002) have also been described within this spectrum of symptoms, as has damage to higher visual functions that may result in difficulties in visuospatial analysis, recognition, simultaneous perception and visual memory (Koeda & Takeshita 1992).…”
Section: Introductionmentioning
confidence: 99%